Infection Surveillance Protocol for a Multicountry Population-based Study in South Asia to Determine the Incidence, Etiology and Risk Factors for Infections Among Young Infants of 0 to 59 Days Old - Islam, Mohammad Shahidul; Baqui, Abdullah H; Zaidi, Anita K; Bhutta, Zulfiqar A; Panigrahi, Pinaki; Bose, Anuradha; Soofi, Sajid B; Kazi, Abdul Momin; Mitra, Dipak K; Isaac, Rita; Nanda, Pritish; Connor, Nicholas E; et al. (The Pediatric infectious disease journal, 2016)
Insufficient knowledge of the etiology and risk factors for community-acquired neonatal infection in low-income countries is a barrier to designing appropriate intervention strategies for these settings to reduce the burden and treatment of young infant infection. To address these gaps, we are conducting the Aetiology of Neonatal Infection in South Asia (ANISA) study among young infants in Bangladesh, India and Pakistan. The objectives of ANISA are to establish a comprehensive surveillance system for registering newborns in study catchment areas and collecting data on bacterial and viral etiology and associated risk factors for infections among young infants aged 0-59 days. We are conducting active surveillance in 1 peri-urban and 4 rural communities. During 2 years of surveillance, we expect to enroll an estimated 66,000 newborns within 7 days of their birth and to follow-up them until 59 days of age. Community health workers visit each young infant in the study area 3 times in the first week of life and once a week thereafter. During these visits, community health workers assess the newborns using a clinical algorithm and refer young infants with signs of suspected infection to health care facilities where study physicians reassess them and provide care if needed. On physician confirmation of suspected infection, blood and respiratory specimens are collected and tested to identify the etiologic agent. ANISA is one of the largest initiatives ever undertaken to understand the etiology of young infant infection in low-income countries. The data generated from this surveillance will help guide evidence-based decision making to improve health care in similar settings.